Plastic Bag Ban Policy in Thailand: A Step into the 20-Year Roadmap for Plastic Waste Management - Mangmeechai, Aweewan (NIDA Case Research Journal, 2022)
In August, 2019, Mariam, a dugong, died due to the many plastic bags found her stomach. Her death stimulated the current campaign to reduce plastic waste. In July 2019, the Cabinet approved a plastic waste management roadmap for 2018–2030. Starting January 1, 2020, the government enacted a ban on free plastic bags. Seventy five of Thailand’s key retailers are participating in this program after signing onto a plastic bag reduction policy to cease offering free plastic bags with purchases. As a result of this policy, Warawut Silpa-archa, Minister of Natural Resources and Environment, expects to see a reduction of 0.78 million tons of plastic waste. Many sectors have questioned the seriousness of this policy’s enforcement because the campaigners find that there are still loopholes in solving this problem. This case study attempts to address the conflicts between the estimates of the amounts of plastic produced, plastic waste generation, plastic waste management (reuse and recycling), the 20-year roadmap, and plastic bag management policies in foreign countries. It compares the environmental impacts of plastic and paper bags and other challenges blocking the success of this new policy. This paper takes the position of an non-governmental organization (NGO) that has monitored government policies by examining claims of the effects of this new policy, data validation, determination of data uncertainty, analysis of the overall picture of this policy with the 20-year roadmap of plastic waste management and assessing the pros and cons of this policy and providing suggestions for the government.